The effect of ethnomathematics-based PBL models on problem solving ability in terms of student learning styles - Widyaningsih, Estina; ‘Adna, Syita Fatih; Chasanah, Aprilia Nurul (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to analyze the influence of differences in learning models on problem-solving ability, the influence of differences in student learning styles on problem-solving ability, and the interaction between learning models and student learning styles on problem-solving ability. The design of this study is a pseudo-experimental design. The samples in this study were students of class VII A and class VII C of SMP Negeri 3 Muntilan who were selected by cluster random sampling. Based on the results of the hypothesis test conducted with the two-way ANAVA test, the results were obtained that 1) there were differences in the influence of learning models on problem-solving ability; 2) there is no difference in the influence of the four learning styles on problem-solving ability; 3) there is no interaction between the learning model and the student’s learning style on problem-solving ability. The conclusions of this study are 1) students with ethnomathematics-based PBL models have better problem-solving abilities than students with direct learning models; 2) students with convergent, divergent, assimilated, and accommodation learning styles with an ethnomathematics-based PBL models have better problem-solving abilities than students with direct learning models.